Perceived Need, Unmet Need for Mental Health Care and Related Factors Among Mothers of Children with Autism Spectrum Disorder in Hamadan, Western Iran - Ayubi, Erfan; Seyedi, Mahdieh; Shafiei, Roya; Jenabi, Ensiyeh (Current Women's Health Reviews, 2025)
BackgroundThere is no reliable data on the perceived need of mothers of children with autism spectrum disorder (ASD) for mental services, and it is unclear how much of mothers' needs are met in Western Iran.ObjectivesThis study aimed to quantify the perceived need and avoidance/delay for mental health care among mothers of children with ASD and also to elucidate the factors associated with perceived need and avoidance/delay.MethodsThis is a cross-sectional study involving all mothers of children with ASD in Hamadan City, Western Iran. Socio-demographic characteristics, depression, anxiety, stress as well as perceived need and avoidance/delay, and associated factors were obtained using researcher-made and standard validated questionnaires. Penalized logistic regression analysis via data augmentation was used to estimate the odds ratio (OR) and 95% confidence interval (CI).ResultsIn total of 103 mothers, approximately 75% and 61% of mothers reported a perceived need and avoiding/delaying needed services during the past 12 months, respectively. Psychological stress and lower family income were significant determinants of the perceived need for mental health care. Minimization (OR: 6.06; 95% CI: 1.33-27.68), low perceived treatment effectiveness (4.40; 1.05-18.35), and financial barrier (4.26; 1.01-17.86) were the most important reasons for avoiding/delaying needed services, respectively.ConclusionThe prevalence of perceived needs and unmet needs is high. Effective psychosocial interventions should be provided to reduce the mental health care gap among mothers of children with ASD.
Keywords: clinical anxiety